Resolution of Disputes in Infrastructure Projects: A Norwegian Perspective - Omar K. Sabri; Olav Torp; Amund Bruland (Buildings)
The resolution of disputes is one of the most critical aspects of construction projects as it directly impacts the success of construction projects. The standard methods in which conflicts are usually resolved in the construction industry in Norway include negotiation, mediation, and litigation. Standard methods used at the international level include negotiation, mediation, and arbitration. This research work tried to establish the effectiveness of different dispute resolution mechanisms in Norway by conducting interviews with professionals dealing with construction disputes. Our study has found that PRIME is the most preferred approach in the Norwegian construction industry because it mainly focuses on negotiations and mediation, while lawsuits are the least preferred. It is in light of the excellent dispute resolution methods that the study should be tailor-made for the specific dispute and include all parties. Such findings would be significant as they would help in coming up with more appropriate dispute resolution mechanisms and, therefore, benefit the construction professionals and policymakers and furnish valuable insight into the field.